Clinical presentation and echocardiographic characteristics of Uhl's anomaly. Issue 2 (29th December 2016) - Mihos, Christos G.; Larrauri‐Reyes, Maiteder; Yucel, Evin; Santana, Orlando
Abstract : Uhl's anomaly is a rare cardiac malformation that results in partial or complete absence of the right ventricular myocardium. It most commonly presents in prenatal or newborn infants; however, it may also be found in some adults as advanced right‐sided heart failure. Differential diagnoses include arrhythmogenic right ventricular dysplasia and Ebstein's anomaly. Herein, we describe the clinical presentation of Uhl's anomaly in a previously undiagnosed middle‐aged adult, and review the echocardiographic criteria used to diagnose and differentiate this rare, albeit important, myocardial disorder.